Penilaian Kinerja Instansi Pemerintah Berdasarkan Balanced Scorecard (BSC) (Kajian dalam Manajemen Publik) - Hasan, Yummil (Universitas Islam Negeri Imam Bonjol Padang, 2015)
Performance assessment can be described as a study of the ability of an organization in achieving goals. The performance assessment can be used to measure the activities of the company / organization in achieving goals and also as material for future improvement. Organizational performance is a performance and the process of implementation in which the organization's objectives to be achieved. In the context of this assessment, which is defined as the performance is to see to what extent the achievement in the achievement of the performance of government agencies in achieving the goals set by the Balanced Score Card (BSC) of the Financial Perspective, Customer Perspective, Internal Processes, Learning and Growth perspective. Thus, performance measurement is a useful tool in efforts to achieve the goals, performance measurement can be done through the process of assessment of the achievement of the set objectives and performance measurement can provide an objective assessment in management decision making. Measurement of performance assessment can help improve the quality and lower the costs arising from the activities of government agencies.